O que informa as políticas públicas: Survey sobre o uso e o n\~ao uso de evidências pela burocracia federal brasileira - Natália Massaco Koga; Pedro Lucas de Moura Palotti; Bruno Gontyjo do Couto; Maricilene Isaira Baia do Nascimento; Rafael da Silva Lins (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The present Text for Discussion aims to present the main results of applied research with the federal bureaucracy in direct administration to understand the uses of different sources of information in policy making. At all, 2,180 questionnaires were answered in the period from October to December 2019. The results point out different profiles of functions performed by bureaucrats, with emphasis on a profile dedicated to the production of government analysis and advisory. As for the mobilization of informational sources, there are four types: those that rely on information produced by Public Administration, others that are based on different forms of external information, a third type that uses information from academic sources and, finally, a profile that have more confidence in personal sources. In relation more specifically to scientific evidence, the credibility and prestige of the source and the applicability of the studies are factors that increase its use at the federal bureaucracy. From an organizational point of view, there are few strategies for the incorporation and dissemination of an evidence-based public policies approach. Efforts to use scientific evidence were found mainly in the individual level.
Keywords: L38; D73; D83; 330; policy making; decision making in public policies; evidence based public policy; bureaucracy; federal public administration; Brazil